Continuing professional development in teachers: insights for designing a formative trajectory in scientific education - Merino, Cristian; Pacheco, Gabriela; Arenas-Martija, Andoni; Becerra, Rukmini; Solís-Pinilla, Jaime (Frontiers in Education, 2025)
This research on Continuing Professional Development (CPD) was conducted through a meticulous and structured systematic review. Initially, four academic databases were explored, merging key terms in both Spanish and English, identifying 1,942 articles. After a preliminary screening, publications were discarded for various reasons: duplication, access restrictions, irrelevance, or exceeding the 10-year age limit, reducing the corpus to 722 articles. A subsequent content review pinpointed only 100 articles directly relevant to CPD studies. A final review assessed thematic depth, research status, and educational relevance, leading to further exclusion and a consolidated set of 81 publications ready for an in-depth review. These articles, selected through a rigorous process, represent current and significant contributions to CPD knowledge in the academic context. All information is organized following the PRISMA 2020 guidelines. The methodology employed ensures the relevance and timeliness of the selected literature, providing a solid foundation for future research in the field and for the design of a Professional Development Program. It is concluded that implementing a CPD program focused on scientific and socially relevant topics requires a strategic combination of pedagogical innovation, expert collaboration, technological integration, and research orientation. These elements prepare teachers to face contemporary challenges and position them as agents of change in their disciplines and communities.